2014
DOI: 10.1260/1759-3131.5.4.189
|View full text |Cite
|
Sign up to set email alerts
|

A Field Study of Atmospheric Icing Analysis in a Complex Terrain of the High North

Abstract: Analyses of atmospheric icing events hold the key for computing the significant parameters leading to icing load calculations. In the cold regions of the high north, atmospheric icing loads on structures become important when it comes to design and safety of infrastructures. Furthermore, icing load calculations over a certain period of time provide a vital input for designers to improve the safety of structures. Patterns of icing events can be evaluated in correlation with other meteorological parameters such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…However, it does not mention other types of icing evolution while we achieve a more detailed and complete result in this wok. Rashid [37] studies the atmospheric icing in a complex terrain and plots an evolution curve of the daily average ice load growth based on the records within a period of 31 days. However, the measurement object may not be fixed as it considers the average ice load in a region while the present paper focuses on the wire.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it does not mention other types of icing evolution while we achieve a more detailed and complete result in this wok. Rashid [37] studies the atmospheric icing in a complex terrain and plots an evolution curve of the daily average ice load growth based on the records within a period of 31 days. However, the measurement object may not be fixed as it considers the average ice load in a region while the present paper focuses on the wire.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of aircraft industry, the degradation of aircraft due to ice accretion on aircraft wings is a major concern, thus the study of the icing evolution makes sense to the detection and de-icing system [33,34]. In the field of atmospheric icing, people also concentrate on the entire icing process, because it can be used as a base for development of more detailed prediction models and the icing load over a certain period of time can provide a vital input for designers to improve the safety of structures [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…[57] revealed that the n of registered birds migrating through the WF area was low, where the average num Risk 4 (Ice throw). A field study shows that the daily intensity of icing in Narvik, a city close to the WF, is approximately 14.5-18.5 kg/m 2 during January, February, and March, as shown in Figure 11 [56]; those measurements can be assumed close enough to be applicable to the site under consideration. This indicates a light icing intensity with site icing index for the WF site, according to Table 1.…”
Section: Risk 4 (Ice Throw)mentioning
confidence: 99%
“…Data include environmental information (pressure, temperature, humidity and wind speed and direction) at the specified location and information on the specific studied phenomenon such atmospheric icing [1]. Wind profiles are closely related with the terrain type and complexity of the topology [1,2]. In the case of ice accretion on wire, relating to instrument performance, the data include ice load, ice type, register of real time appearance of the ice, tension and torsion of the wire elements, electrical variables like electrical current, resistance (when applied) and power loss.…”
Section: Numerical Simulation Mediamentioning
confidence: 99%